Marketing Research for Managers / Second Edition - Crouch Sunny; Housden Matthew (Butterworth Heinemann, 1996)
An easy-to-read, practical introduction to Marketing Research. Foreword, Preface, Acknowledgements, Introducing Marketing Research, Getting Started, Marketing Research Begins at Home, How are the Data Collected, How Do We ask the Questions, What Happens to the Answers, Using Research in Industrial Markets, Using Research in Experiments, Using Research in International Markets, Where Do you Go From Here, Index.